Autistic Traits in Schizophrenia Spectrum Disorders - Šustová, Petra; Rodriguez, Mabel (Current Psychiatry Research and Reviews, 2022)
Background: In recent years, there has been an emerging interest in the overlap between schizophrenia and autism. The co-occurrence between these two disorders may be seen not only at a diagnostic level but also as the presence of autistic traits in schizophrenia. There has been a rapid rise in the number of studies focusing on autistic traits in schizophrenia and their clinical associations. Objective: Here, we provide a review that summarizes the current findings and highlights gaps that may be addressed by future research. Results: Higher levels of autistic traits have been associated with earlier age of onset, longer duration of illness, resistance to treatment, and more severe cognitive deficit. However, regarding social cognition and psychosocial functioning, the findings are mixed. Conclusion: Patients with prominent autistic traits seem to be more affected. The effect of autistic traits on social cognition and psychosocial functioning remains unclear, as does their relationship with negative symptoms. Therefore, longitudinal studies are highly needed.
Keywords: Schizophrenia